THE RELATIONSHIP BETWEEN COMMUNITY WELFARE AND CRIME IN EAST JAVA 2019-2022 - Nadiva Aulia Eka Anggraini; Inda Fresti Puspitasari (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study investigates the impact of community welfare on criminality in East Java Province. The dimensions ofized in the welfare used in this study are education, unemployment, poverty, and health. The study uses panel data collected from the Central Statistics Agency (BPS) and applies panel data regression analysis to measure the real effect of each of these socioeconomic variables on criminality. The results suggest the presence of a positive and significant impact of education on crime and of poverty, with a negative and significant effect. Employment and health indicators, on the other hand, do not show a statistically significant effect on crime. These results suggest that improving education without enough job opportunities may increase the chances of criminal behavior. At the same time, poverty continues to drive crime due to ongoing economic pressures. Overall, the study points out the need to improve the quality of education and its connection to the job market while also focusing on strategies to reduce poverty. Community-based economic empowerment is crucial in efforts to lower crime in East Java.